SIMULTANEOUS DETERMINATION OF PARACETAMOL, PSEUDOEPHEDRINE HYDROCHLORIDE, AND DEXTROMETHORPHAN HYDROBROMIDE IN TABLETS USING MULTIVARIATE CALIBRATION METHODS COUPLED WITH HPLC-DAD - Asci, Burge; Donmez, Ozlem Aksu; Bozdogan, Abdurrezzak; Sungur, Sidika (TAYLOR & FRANCIS INC, 2011)
A new method using high performance liguid chromatography (HPLC) with diode array detection (DAD) was developed and validated for the simultaneous determination of paracetamol (PAR), pseudoephedrine hydrochloride (PSE), and dextromethorphan hydrobromide (DEX) in tablets. The spectrochromatograms of these compounds give the severely overlapping spectrochromatogram. This makes the use of univariate calibration impossible. Therefore, PLS and PCR were used to analyze the three-way data recorded by HPLC-DAD. These multivariate calibration methods were tested by analyzing the synthetic mixtures of PAR, PSE, and DEX. The recoveries were in the range of 96.1-100.2% and 97.1-100.4%, relative error of prediction (REP%) in the range of 0.5-6.7 and 0.8-7.0% were obtained for PLS and PCR, respectively. These methods were also applied to real samples containing the three drugs, and recoveries in the range of 99.0-106.0% and 99.6-106.3% were obtained for PLS and PCR, respectively. The results obtained by PLS and PCR statistically compared with the results obtained by the classical HPLC method. It was found that there were no significant differences between the means and the standard deviations of the results obtained by the multivariate calibration methods and classical method. HPLC-multivariate calibration methods have several advantages over the classical HPLC method. These advantages are the use of a simple mobile phase and shorter analysis time. Also, these methods do not require the internal standard and the gradient elution.
Keywords: dextromethorphan hydrobromide; HPLC-DAD; paracetamol; partial least squares; principal component regression; pseudoephedrine hydrochloride; PARTIAL LEAST-SQUARES; SPECTROPHOTOMETRIC MULTICOMPONENT ANALYSIS; PERFORMANCE LIQUID-CHROMATOGRAPHY; PHARMACEUTICAL-PREPARATIONS; LIDOCAINE HYDROCHLORIDE; ACTIVE INGREDIENTS; MIXTURE; QUANTITATION; TRIPROLIDINE; GROUNDWATER; Biochemistry & Molecular Biology; Chemistry